Robust Versus Optimal Rules in Monetary Policy : A Note. (IMF Working Papers; Working Paper ;, 2004)
We provide a framework for analyzing the choice between optimal and robust monetary policy rules in the presence of paradigm uncertainty. We first discuss the conditions on uncertainty that render a robust rule preferable to an optimal rule. Second, we show how the degree of risk aversion of the policymaker increases the region in which the robust rule is preferred.